Identification of Quinazolinone Analogs Targeting CDK5 Kinase Activity and Glioblastoma Cell Proliferation - Peyressatre, Marion; Arama, Dominique Patomo; Laure, Arthur; González-Vera, Juan A.; Pellerano, Morgan; Masurier, Nicolas; Lisowski, Vincent; Morris, May C. (Frontiers in Chemistry, 2020)
CDK5/p25 kinase plays a major role in neuronal functions, and is hyperactivated in several human cancers including glioblastoma and neurodegenerative pathologies such as Alzheimer’s and Parkinson’s. CDK5 therefore constitutes an attractive pharmacological target. Since the successful discovery and development of roscovitine, several ATP-competitive inhibitors of CDK5 and peptide inhibitors of CDK5/p25 interface have been developed. However these compounds suffer limitations associated with their mechanism of action and nature, thereby calling for alternative targeting strategies. To date, few allosteric inhibitors have been developed for successful targeting of protein kinases. Indeed, although this latter class of inhibitors are believed to be more selective than compounds targeting the active site, they have proven extremely difficult to identify in high throughput screens. By implementing a fluorescent biosensor that discriminates against ATP-pocket binding compounds to screen for allosteric inhibitors that target conformational activation of CDK5, we have identified a novel family of quinazolinones. Characterization of these hits and several of their derivatives revealed their inhibitory potential towards CDK5 kinase activity in vitro and to inhibit glioblastoma cell proliferation. The quinazolinone derivatives described in this study are the first small molecules reported to target CDK5 at a site other than the ATP pocket.These compounds offer alternatives to conventional ATP-competitive inhibitors or peptides targeting CDK5/p25 interface with the potential of bypassing their limitations.